Evaluation of in silico anticancer activity of some striazine derivatives as VEGFR2 inhibitors - Tuyen, Truong Ngoc; Vi, Le Thi Tuong; Em, Pham Canh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
The s-triazine derivatives have been shown to have diverse biological activities, especially anticancer activity. Fifty s-triazine derivatives were screened for anticancer activity through inhibition of VEGFR2 (vascular endothelial growth factor receptor-2) by molecular docking method using AutoDock Vina software. Compounds 20 and 40 showed the strongest interactions among all tested compounds with the binding affinity values of -10.8 and -10.5 Kcal/mol, respectively compared to reference drugs Gedatolisib (-9.1 Kcal/mol) and Paclitaxel (-7.8 Kcal/mol) at the active site of VEGFR2. These compounds established one carbon-hydrogen bond at amino acid HIS1026, specifically exhibiting better electrostatic and hydrophobic interactions than the reference drugs Gedatolisib and Paclitaxel. Moreover, compounds 20 and 40 also showed interactions with the VEGFR2 receptor that resemble the reference drug Gedatolisib at amino acids such as ARG1027, ASP1046, and HIS1026. Therefore, these compounds could be a potential lead molecule for anticancer activity.